Tindak Pidana Zina dan Penuduhan Zina: Kajian Hukum Pidana Islam - Noor Izzati Amelia; Radiatus Sholehah; Khairunnisa Khairunnisa (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Zina and accusations of adultery (qadzaf) are two central themes in Islamic criminal law. This research examines the definition, proof, and sanctions of zina and qadzaf from the perspective of Islamic criminal law using the literature method. Zina is defined as sexual intercourse outside a legal marriage, while qadzaf is accusing adultery without sufficient evidence. In Islam, adultery is proven by four witnesses, confession of the perpetrator, or other supporting evidence. The punishment for muhsan adulterers (married) is stoning, while ghairu muhsan (unmarried) are flogged 100 times. Meanwhile, qadzaf can be proven by four witnesses, confession of the perpetrator, or an oath (according to Imam Shafi'i). The punishment is 80 lashes and the testimony of the perpetrator is not accepted. Islamic criminal law strictly regulates adultery and qadzaf with high evidentiary requirements and severe sanctions. This type of research is a qualitative literature study and uses a descriptive analysis method, namely by analyzing various sources and relevant data. The existence of this prohibition of adultery and qadzaf aims to prevent harm, maintain honor, and uphold the benefit (maqashid sharia).